Odor Markers of Poetical Speech of the Beginning of the XX Century - Cherevchenko, Oleksandr (Ukrainian linguistics, 2019)
The article deals with an attempt to characterize a smell in human knowledge, analyzed the points of view of different scientists concerning this problem, considered odor markers of the artistic text as components of united system of verbal and non verbal individual resources aimed at forming different types of subtext. The olfactory feeling occupies the special place in the vital functions of man. They arose up one of the first, next to taste, which provided the living organisms two basic functions: feed and reproduction. However, in the process of evolution, olfactory feelings experienced the biggest changes European poetry of the beginning of XX century is interesting in its aspiration to create a new poetical speech that is why the attention is adhered to odor instruments, when the smell became an expression of the esthetical subtext. Odor content of the poetical speech of the XX century is one of the most important tools of forming content deepness of the text meaning, disclosure of the palette of meanings. The research is based on the material of poetry of representatives of Silver age and Ukrainian neoclassicists. The research proves that the most dynamic is lexical system of the language which helps to show ethnic language map of the world in artistic text. It studies the evolution of an individual author’s nomination in the poetic creativity of M. Rylsky, M. Zerov, Y. Klen, M. Dray-Hmara, P. Fylypovych, A. Block, N. Gumilov, A. Akchmatova, V. Maiakovski, S. Jesenin, V. Chlebnikov, O. Mandelshtam, M. Zvietaieva, V. Briusov and others. The paper examines the semantic-derivative structure of innovations of odor lexems, classifies the most numerous lexical and semantic groups of new words for identifying smell, and defines typical signs of odorous lexemes that represent the specific national language and poetic view of the world. Materials of the research can be used in teaching such subjects as “Modern Ukrainian Literary Language (lexicology, phraseology, lexicography)”, “Stylistics and Culture of the Ukrainian Language”, “Rhetoric and Linguistic Analysis of Artistic Text”, as well as special courses on ethnolinguistics, linguopoetics; for writing chapters devoted to the study of trope units, in textbooks and manuals; in lexicographic practice when compiling dictionaries of the writer’s language. Information about the author: Oleksandr Cherevchenko – PhD, Associate Prof., Pavlo Tychyna Uman State Pedagogical University (Ukraine). E-mail: o.m.cherevchenko@udpu.edu.ua __________ References Ball Kh. (1986) Manifest k pervomu vecheru dadaistov v Tsyurihe [Manifest by the first evening of Dadaists in Zurich]. Nazyivat veschi svoimi imenami: Programmnyie vyistupleniya masterov zapadnoevropeyskoy literaturyi XX veka. Moskow: Progress, pp. 316-317 (in Russian). Beletskiy A.I. (1964) Izbrannyie stati po teorii literatury [Selected articles on the theory of literature]. Moskow: Prosveschenie, 478 p. (in Russian). Budagov R.A. (1971) Istoriya slov i istoriya obschestva [The history of words and the history of society]. Moskow: Prosveschenie, 248 p. (in Russian). Haidaienko I. (2003) Stylistychni funktsii nazv smaku y zapakhu v poeziiakh Yara Slavutycha [Stylistic functions of the names of taste and smell in Yar Slavutych’s poetry]. Poetyka Yara Slavutycha (ed. I. Lopushynskyi). Kherson, pp. 197-211 (in Ukrainian). Halchuk O. (1997) Poetychne osmyslennia Mykoloiu Zerovym svitovoi kulturnoi spadshchyny [Poetical Understanding by Mykola Zerov of the World Cultural Heritage]. Dyvoslovo, no 8, pp. 5-7 (in Ukrainian). Hundorova T. (1997) Proiavlennia Slova. Dyskursiia rannoho ukrainskoho modernizmu. Postmoderna interpretatsiia [Manifestation of the Word. The Discourse of Early Ukrainian Modernism. Postmodern interpretation]. Lviv, 237 p. (in Ukrainian). Diatchuk V.V. (1978) Yak peredaietsia v movi vidchuttia zapakhu [How is the sense of smell transmitted in the language]. Kultura slova, vol. 15, pp. 35-42 (in Ukrainian). Korchova-Tyurina S.N. (2001) Problema marginalnyih form v evropeyskoy kulturnoy sensorike [The problem of marginal forms in the European cultural sensor] (PhD Thesis). Harkov, 223 p. (in Russian). Pluzhnikov M.S., Ryazantsev S.V. (1991) Sredi zapahov i zvukov [Among the smells and sounds]. Moskow: Molodaya gvardiya, 213 p. (in Russian). Pluzhnikova T.I. (2004) Aromatizmyi v yazyike i rechi: k postanovke problemyi [Aromasms in anguage and speech: to the problem statement]. Visnyk Umanskoho peduniversytetu. Filolohiia movoznavstvo). Kyiv: Znannia Ukrainy, pp. 171-177 (in Russian). Zinchenko V.P., Mescheryakova B.G. (eds.) (2001) Psihologicheskiy slovar [Psychological Dictionary]. Moskow: Pedagogika Pres, 440 p. (in Russian). Timofeev L.I., Turaev S.V. (1974) Slovar literaturovedcheskih terminov [Dictionary of Literary Terms]. Moskow: Prosveschenie, 487 p. (in Russian). Stavytska L. O. (2000) Estetyka slova v ukrainskii poezii 10-30 pp. XX st. [Aesthetics of the word in Ukrainian poetry in 10-30 th of XX century]. Kyiv: Pravda Yaroslavychiv, 156 p. (in Ukrainian). Franko I. Ya. (1980) Iz sekretiv poetychnoi tvorchosti. Zibr. tvoriv: U 50 t. [From the secrets of poetic creativity]. Vol. 37. Kyiv: Naukova dumka, 489 p. (in Ukrainian). Shapar V. (2004) Psykholohichnyi tlumachnyi slovnyk [Psychological Explanatory Dictionary]. Kharkiv: Prapor, 365 p. (in Ukrainian).